Exploring students’ health awareness of personal hygiene and dietary behaviors in primary education in Qatar - Nasser Mansour; Aisha Alfojery (Critical Public Health)
Unhealthy dietary habits and poor personal hygiene remain persistent challenges among primary school students. This study examined health awareness about personal hygiene and dietary habits among 431 students (267 boys, 164 girls) in grades 4–6 at five Qatari public schools. Schools were selected via convenience sampling, with Ministry of Education collaboration, to ensure regional representation. Students completed a validated questionnaire about hygiene behaviors and dietary habits. The data were analyzed using descriptive statistics, Mann-Whitney U tests, Kruskal-Wallis tests, and multiple regression analysis. Results showed a clear link between hygiene and diet: students with better hygiene habits also had healthier eating patterns. Dietary behaviors differed by gender, but hygiene awareness was similar between boys and girls. We found misconceptions, such as misunderstandings about posture’s impact on spine health and limited awareness of disease prevention. These findings emphasize the need to integrate health and hygiene education into primary science curricula, fostering lifelong well-being.